2010
DOI: 10.1007/s00345-010-0561-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral anticoagulation on morbidity of transurethral resection of the prostate

Abstract: OA had a significant and independent impact on TURP outcome in terms of bleeding complications. This data could be used for treatment decision and for patient's information prior BPH surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 17 publications
0
36
1
8
Order By: Relevance
“…Shah et al [30] have observed that preoperative prostate volume, intraoperative duration of irrigation, total amount of irrigation fluid used and weight of resected prostatic tissue directly influence the amount of fluid absorption during HoLEP. Finally, the transfusion rates in this study after ThuVEP (3.9%) and ThuVARP (0%) in cardiopulmonary high-risk patients on OA are comparable to PVP (0-2%) [2,11,12,13,14,15,16], HoLEP (0-9.6%) [17,18,31], and lower than in current TURP studies (up to 11%) [6,7,8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shah et al [30] have observed that preoperative prostate volume, intraoperative duration of irrigation, total amount of irrigation fluid used and weight of resected prostatic tissue directly influence the amount of fluid absorption during HoLEP. Finally, the transfusion rates in this study after ThuVEP (3.9%) and ThuVARP (0%) in cardiopulmonary high-risk patients on OA are comparable to PVP (0-2%) [2,11,12,13,14,15,16], HoLEP (0-9.6%) [17,18,31], and lower than in current TURP studies (up to 11%) [6,7,8]. …”
Section: Discussionmentioning
confidence: 99%
“…The surgical management of BPO is complicated by an increasing use of oral anticoagulants (OA) for primary and secondary prevention of cardiovascular complications [2]. However, a controversy exists regarding the performance of TURP under OA: while transfusion rates up to 28.6% have been found in older series [3,4,5], these transfusion rates could not be confirmed in more recent studies with transfusion rates up to 11% [6,7,8]. Various, more minimally invasive laser devices have been introduced as alternatives to TURP for the surgical treatment of BPO during the past 20 years [9,10]: the potassium-titanyl-phosphate (KTP) [2,11,12,13,14,15,16], the holmium:YAG [17,18], and the thulium:YAG [19,20,21] laser.…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, the cohort of patients who stopped their medication (n = 105) in the report by Raj et al [16] was too small to draw significant conclusions regarding morbidity. In a multicenter analysis from France, patients undergoing TUR-P under OA were compared to a cohort without OA [2]. Most patients stopped OA or were bridged to heparin.…”
Section: Discussionmentioning
confidence: 99%
“…acetylsalicylic acid and clopidrogel following drug eluting stent in coronary disease or phenprocoumon in atrial fibrillation) because the risk of bleeding complications is significantly elevated [2]. In order to perform TUR-P, the medication is often interrupted or bridged with low-molecular-weight heparin.…”
Section: Introductionmentioning
confidence: 99%
“…Oral anticoagulant (OAC) use is increasing. Descazeaud and colleagues reported that 33% of men listed for bladder outlet surgery were taking an OAC [Descazeaud et al 2011]. Although most urologists would recommend stopping these agents perioperatively, this is not without risk, and even if they are stopped there remains a significant risk of bleeding with M-TURP [Tyson and Lerner, 2009].…”
Section: Bipolar-turp (B-turp)mentioning
confidence: 99%